Obsessive-compulsive disorder - Zohar, J; Zohar, J (Chichester, West Sussex John Wiley & Sons, 2012)
"A clear summary of what is known about a highly prevalent and debilitating disorder that affects nearly as many people as does asthma. Expert authors review the biological basis for the disorder and describe both pharmacological and psychological approaches to treatment"--Provided by publisher.
Methodological Issues for Clinical Treatment Trials in Obsessive-Compulsive Disorder / Samar Reghunandanan and Naomi A. Fineberg -- Serotonin and Beyond: A Neurotransmitter Perspective of OCD / Anat Abudy ... [et al.] -- Brain Imaging / David R. Rosenberg, Phillip C. Easter, and Georgia Michalopoulou -- The Genetics of Obsessive-Compulsive Disorder: Current Status / David L. Pauls -- Neurocognitive Angle: The Search for Endophenotypes / Samuel R. Chamberlain and Lara Menzies.
Keywords: Obsessive-Compulsive Disorder; Obsessive-Compulsive Disorder; Obsessive-Compulsive Disorder